Komunikasi Transbudaya Pondok Pesantren: Kajian Teoretis dalam Paradigma Konstruktivis - Kun Wazis (Institut Ilmu Sosial dan Manajemen STIAMI, 2017)
An intercultural communication that occurs in a boarding school (pesantren) environment is a unique phenomenon. A number of pesantrens in Indonesia apply a pattern of multicultural education. Therefore, their students (santri) understand different culture of students who come from different cultural background. Through literature review and theoretical studies in constructivist paradigm, it can reveal a number of interesting scientific realities about transcultural communication of boarding schools in Indonesia. First, the students of different cultures understand each other and they make friends well during their study at the pesantren. Secondly, kyai has a strong influence in conveying messages of intercultural communication among santri by using pesantren symbols. Third, pesantren cultivation develops multicultural education based on Islamic teachings that understand plurality in human relations. Fourth, the boarding school environment can communicate a multicultural communication message through pesantren network, both national and international so they can build the spirit of togetherness in the diversity.